Camel Milk Attenuates Hepatic Inflammation in Monosodium Glutamate-Exposed Rats - Adefisayo, M. A.; Folawiyo, M. A.; Oni, T. M.; Ajayi, A. F. (Journal of Science, Technology and Innovation Research, 2026)
Monosodium glutamate (MSG), is a white crystalline food addictives. Evidence indicates MSG as an inducer of hepatic inflammation. Camel milk is a natural dietary product with antimicrobial, antioxidant, and immunomodulatory properties. Hence this study aimed to evaluate the effects of camel milk on hepatic inflammatory markers in MSG-exposed male rats. The study involved 24 rats divided into four groups with average weight of 195g, Group A is the control and received distilled water (1ml/kg body weight), group B received (MSG) (6g/kg), group C received Camel milk (5ml/kg) 15minutes after MSG administration and group D served as the recovery group left for 21days without any treatment. The assessment of hepatic damage involved measuring inflammatory markers which includes myeloperoxidase, nitric oxide, C-reactive protein, Tumor Necrosis Factor-α, interleukin-1β, Nuclear factor kappa B.s MSG exposure significantly increased serum inflammatory markers and histological changes compared to the control group indicating hepatic inflammation. However, treatment with camel milk led to a significant decrease in these markers and improved histopathological outcomes. The recovery group exhibited suppressed levels of inflammatory markers, but more pronounced in the camel milk group. The study provides evidence for the anti-inflammatory effects of camel milk on hepatic inflammatory markers in MSG-induced hepatic inflammation. These findings enhance our understanding of MSG’s harmful effects and highlight the potential of camel milk as a natural therapeutic agent for liver inflammation. Keywords: Monosodium glutamate, camel milk, inflammatory markers, liver histology.